Hubungan Antara Penggunaan Kontrasepsi Oral Kombinasi Dengan Kejadian Melasma di Kecamatan Grogol Sukoharjo - Elviana, Marlina, Dr. Ratih Pramuningtyas, Sp.K.K (2017)
Back ground: Melasma is a pigmentation disorder due to the increased of melanin in the epidermis and dermis as a patch of uneven and the color is light brown to dark brown. Causative factor of melasma included estrogen and progesterone contained in the combined oral contraceptive pill. Objective: To understanding the relationship between the usage of the combined oral contraceptive and melasma. Methods: The type of this research is observational analytic and it uses cross sectional approach. The total number of respondents is 60 women who qualified with restriction criteria. Within this research, there are few measuring instruments are used namely questionnaires and direct diagnosed by a dermatologist and then it is assessed based on MASI score.The data analysis using statistical test which is contingency coefficient. Result: From 30 people who used oral contraceptive, 33,3% were melasma and 16,7% were not have melasma. Meanwhile, from 30 people were not used the combined oral contraceptive, 15% were melasma and 35% were not have melasma. Based on the data, there was a relationship between the usage of the combined oral contraceptive and melasma with p value 0,000 (p<0,05). Conclusion: There was a relationship between the usage of the combined oral contraceptive and melasma. Key words: the combined oral contraceptive, melasma, MASI score, estrogen, progesterone